Muhammadiyah Regional Leadership Da'wah Management in Educating Teenagers About the Dangers of Promiscuity - Nurhaini, Nurhaini; Kustiawan, Winda (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
The purpose of this study is to examine how the Regional Leadership of Muhammadiyah in Medan City manages its da'wah efforts in educating teenagers about the dangers of promiscuous behavior. This research employs a qualitative descriptive method. Data were collected through interviews, observations, and documentation. The data analysis techniques used include data reduction, data display, and conclusion drawing. The findings reveal that the Regional Leadership of Muhammadiyah Medan applies key functions of da'wah management, including planning programs based on youth needs, organizing through the optimization of autonomous organizations such as IPM, IMM, Pemuda Muhammadiyah, and NA, and mobilizing through training, social activities, and the use of social media. Control is implemented through comprehensive evaluations of program execution, materials, methods, and behavioral changes in youth after participating in da'wah activities. The impact of this da'wah management demonstrates its effectiveness in raising spiritual awareness, strengthening character, and fostering the moral resilience of youth amid the flow of permissive culture and digitalization. This research contributes significantly to the development of participatory da'wah models that can be adopted by other religious organizations in addressing contemporary moral challenges faced by youth.